The lost tombs of Thebes life in paradise - Hawass, Zahi A. 1947- (Thames & Hudson, 2009)
Shows the tombs of Thebes, the landscape of the ancient city, and the lives of the nobles who lived there during Egypt's golden age.
Includes bibliographical references and index
Keywords: Geschichte; Tombs / Egypt / Valley of the Kings; Tombs / Decoration / Egypt / Valley of the Kings; Mural painting and decoration, Egyptian / Egypt / Valley of the Kings; Decoration and ornament - Valley of the Kings (Egypt); Mural painting and decoration - Valley of the Kings (Egypt); Tombs - Valley of the Kings (Egypt); Funde; Mural painting and decoration, Egyptian -- Egypt -- Valley of the Kings; Tombs -- Decoration -- Egypt -- Valley of the Kings; Tombs -- Egypt -- Valley of the Kings; Tombs -- Egypt -- Valley of the Kings -- Pictorial works; Grab; Publikum; Sperrung; Wandmalerei; Valley of the Kings (Egypt) / Antiquities; Valley of the Kings (Egypt) / Antiquities / Pictorial works; Valley of the Kings (Egypt) - Antiquities - Pictorial works; Valley of the Kings (Egypt) - Antiquities; Valley of the Kings (Egypt) -- Antiquities; Valley of the Kings (Egypt) -- Antiquities -- Pictorial works; Theben -- Ägypten; Bildband